Pendidikan Kesehatan tentang Penatalaksanaan Non Farmakologi untuk Mengurangi Nyeri Persalinan - Yunika, Regina Pricilia; Ulya, Yadul; Herlina, Siskha Maya (LPPM Universitas Bumigora, 2023)
Labor is the process of expulsion of the fetus that occurs in full-term pregnancies born spontaneously with a rear-head presentation without complications to the mother and fetus. During childbirth, the mother feels pain that can interfere with comfort during contractions. Labor pain appears during the first stage of the active phase. Methods to reduce pain due to labor can be done with pharmacological and non-pharmacological methods. Non-pharmacological will not give side effects to the mother. Non-pharmacological techniques are usually deep breathing relaxation techniques, warm/cold compresses, music therapy, aromatherapy, and massage. Objective: to increase the knowledge of pregnant women about non-pharmacological management to reduce labor pain. Methods: counseling, discussion, question, and answer, as well as pretest and posttest. Result: there is an increase in knowledge of pregnant women who have good knowledge by 29,1%, namely from 62,5% increased to 91,6%. Conclusion: there is an increase in the knowledge of pregnant women about non-pharmacological management to reduce labor pain after receiving health education.